Correction to the paper: An energy dissipative spatial discretization for the regularized compressible Navier-Stokes-Cahn-Hilliard system of equations (in Math. Model. Anal., 25(1): 110–129, https://doi.org/10.3846/mma.2020.10577) - Balashov, Vladislav; Zlotnik, Alexander (Mathematical Modelling and Analysis, 2021)
We correct the proof of Theorem 2 in the mentioned paper concerning finite-difference equilibrium solutions.